Devotional rupture: Bengali Vaiṣṇavism and colonial modernity - Wong, L (2021)
This thesis probes the dynamics of modernity in the context of colonial Hinduism. It challenges prevailing assumptions that the encounter with British colonialism effected a wholesale historical rupture within Hindu traditions and, moreover, that this rupture is constitutive of their modernity. It urges, in sum, that modern Hinduism need not in every case imply a Hinduism severed from its pre-colonial moorings.